Back Cover: Insight into the Interactions between Novel Coumarin Derivatives and Human A3 Adenosine Receptors (ChemMedChem 10/2014). Issue 10 (October 2014) - Matos, Maria João; Vilar, Santiago; Kachler, Sonja; Fonseca, André; Santana, Lourdes; Uriarte, Eugenio; Borges, Fernanda; Tatonetti, Nicholas P.; Klotz, Karl‐Norbert
<x xml:space="preserve">Abstract</x> The back cover picture shows 3‐arylcoumarin analogues targeting A1, A2A, A2B and A3 adenosine receptors (ARs). At the cellular level, most of the compounds proved to be selective A3 AR ligands, which makes them promising development candidates for the treatment of asthma, inflammatory and neurodegenerative diseases, and as protective agents against cardiac ischemia. For more details, see the Full Paper by Maria João Matos et al. on p. 2245 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>